Identidade sociedade-espaço: transformação e permanência na avenida Afonso Pena - Tatiana Pimentel Barbosa (2022)
The 20th century brought an intense acceleration of the transformation of large cities' landscape, which culminated in the development of heritage preservation concepts. In Belo Horizonte, from the mid-1930s, the city began to verticalize and transform itself through a cycle of successive replacements of landscape elements, both strong urban icons and buildings without great prominence in the panorama. This research is based on a case study which analyzes the history of Afonso Pena Avenue's metamorphosis, the main route of the plan to implemente the new Minas Gerias capital in the 19th century and, therefore, witness of the most importante buildings that made up de the inicial landscape of urban ocupation. Despite the transfiguration that the avenue has undergone throughout history, the road crosses time with a strong symbolic charge in the collective imagination, being chosen as the stage for the population's identity expressions, whether on the exceptional scale, as is the case of organized manifestations, or on the scale of the trivial, of people's daily routine. Something exists there that regardless of changes in the physical structure, it guarantees its symbolic potency. The objective is to identify, in its materiality and immateriality, the structure that sustains the continuity of the symbolic force of Afonso Pena Avenue. From the cultural identity concepts formed by the link society-space, the research represents an overall panorama of the transformation of the landscape and analyzes the main cases of icon substitution, verifying the interference of the transformation of each point in the identity interpretation of the avenue landscape.